2010
DOI: 10.1002/rcm.4809
|View full text |Cite
|
Sign up to set email alerts
|

Study of plasma metabolic profiling and biomarkers of chronic unpredictable mild stress rats based on gas chromatography/mass spectrometry

Abstract: A metabolomic investigation of chronic unpredictable mild stress (CUMS) rats was carried out. Plasma obtained from Sprague-Dawley (SD) rats treated by CUMS was analyzed using gas chromatography/mass spectrometry. Thirty-seven metabolites were identified among the detected compounds. Subsequent data analysis using the t test and principal component analysis (PCA) revealed significant metabolic changes in the rats' plasma after CUMS treatment. Clear separation between the model and control group was achieved, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 32 publications
(35 reference statements)
3
45
0
Order By: Relevance
“…Finally, the obtained results were exported to Excel (Microsoft, Redmond, USA), edited and organized into two-dimensional data matrices consisting of variables [retention time (Rt), mass-to-charge ratio (m/z)], observed variables (sample names) and integral areas. After spectrogram integration of samples in three groups, metabolites from serum and liver tissue samples were judged by their consistent detection in at least 80% of the samples [18,19]. The resulting twodimensional matrices were imported into SIMCA-P software 11.0 (Umetrics AB, Umea, Sweden) for multivariate statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the obtained results were exported to Excel (Microsoft, Redmond, USA), edited and organized into two-dimensional data matrices consisting of variables [retention time (Rt), mass-to-charge ratio (m/z)], observed variables (sample names) and integral areas. After spectrogram integration of samples in three groups, metabolites from serum and liver tissue samples were judged by their consistent detection in at least 80% of the samples [18,19]. The resulting twodimensional matrices were imported into SIMCA-P software 11.0 (Umetrics AB, Umea, Sweden) for multivariate statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it can also be found that the true stress decreases with the decreased strain rate. This is becasue the low strain rate offers the long time for the progress of vacancy diffusion, dislocations motion and dynamic recrystallization [40][41][42][43]. Generally, the relationship between grain morphology and stress-strain curve can be analyzed by the evolution of straininduced grain boundary migration, the competitive effect of working hardening and strain softening, etc.…”
Section: High-temperature Deformation Behaviormentioning
confidence: 99%
“…Multivariate metabolomics data could be simplified by PCA to a low-dimensional plot to identify the similarities and differences between the treatment and control groups [14]. All data obtained in this investigation were analyzed by PCA and OPLS-DA ( Fig.…”
Section: Metabolites Analysismentioning
confidence: 99%